2018
DOI: 10.1177/0269881118783314
|View full text |Cite
|
Sign up to set email alerts
|

Energy drinks, caffeine, junk food, breakfast, depression and academic attainment of secondary school students

Abstract: The present findings indicate that consumption of energy drinks is associated with an increased likelihood of poor academic attainment that reflects energy drink consumption being part of an unhealthy diet or being associated with skipping breakfast rather than a more specific effect, such as being a source of caffeine. Although the current study extends previous research by utilising a longitudinal design, intervention studies are now required to better answer questions relating to causality and direction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 38 publications
4
28
1
1
Order By: Relevance
“…ED intake was associated with more frequent consumption of fast food and less regular intake of fruits, vegetables, and breakfast. 26 These findings suggest that there is an association between ED consumption and the risk of following unhealthy dietary choices. Resulting in an increased risk of overweight or obesity among children and adolescents.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…ED intake was associated with more frequent consumption of fast food and less regular intake of fruits, vegetables, and breakfast. 26 These findings suggest that there is an association between ED consumption and the risk of following unhealthy dietary choices. Resulting in an increased risk of overweight or obesity among children and adolescents.…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, other studies showed that consuming sweets and sweet products were positively associated with consuming ED, soft drinks, and high-fat meals. 26 Park et al 19 showed that participants who had EDs five times or more per week were more likely to eat fast food compared with those with infrequent ED intake (less than once a week). ED intake was associated with more frequent consumption of fast food and less regular intake of fruits, vegetables, and breakfast.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that Japanese tend to consume green tea during meals (52) . However, breakfast skippers have been reported to be higher consumers of soft drinks (53) . These may partly explain the present study results that there was no difference of beverage consumption between breakfast consumers and skippers, while breakfast consumers had higher green tea consumption and lower soft drink consumption than breakfast skippers in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…However, Dunn cautioned that in 20th century modernity, zest was being confused with ‘ something that gives us a very momentary “lift” ’ [14]. In the 21st century, the iron pyrite of zest and aliveness is all-too-often sold to the public in the form of “energy” drinks [16].…”
Section: High-level Wellnessmentioning
confidence: 99%